Kubiakowe „Medytacje...” – Janicki zwrócony polszczyźnie - Arndt, Aleksandra (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The article analyzes the translation of the elegy II 2 by Klemens Janicki, made by Zygmunt Kubiak.